Chromium and arsenic synchronous removal-conversion type biomass-based adsorption material as well as preparation method and application thereof

By preparing a synchronous removal-converted biomass-based adsorption material of chromium and arsenic, using amino groups, reduced iron and coconut charcoal and crosslinking reactions of epoxypropane, the problem of difficult to remove hexavalent chromium and trivalent arsenic in the prior art was solved, and efficient heavy metal removal and conversion was achieved, significantly improving the water treatment effect.

CN119838573AActive Publication Date: 2025-04-18GUANGXI UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510048667.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove hexavalent chromium and trivalent arsenic present in industrial wastewater, and the electrically neutral form of trivalent arsenic limits the adsorption effect of amino-modified materials, and the competitive behavior of hexavalent chromium and pentavalent arsenic further complicates water body management.

Method used

A synchronous removal-converting biomass-based adsorption material of chromium and arsenic was used to prepare a material with rich amino adsorption sites and good photothermal photocatalytic properties by introducing amino groups, reduced iron and coconut shell char containing C=C double bonds, combined with crosslinking reaction of epoxypropane. This material not only can efficiently adsorb hexavalent chromium and trivalent arsenic, but also convert it into less toxic trivalent chromium and pentavalent arsenic.

Benefits of technology

The rapid removal of chromium and arsenic in heavy metal wastewater was achieved (20-60 minutes), and the conversion of hexavalent chromium and trivalent arsenic reached more than 95%. The photothermal and photocatalytic properties of the material significantly improved the adsorption rate and conversion efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a chromium and arsenic synchronous removal-conversion type biomass-based adsorption material as well as a preparation method and application thereof, belongs to the technical field of environmental treatment, and solves the problem that chromium and arsenic coexisting wastewater is difficult to treat. The biomass-based adsorption material is a stable heavy metal adsorption material prepared by introducing a high-density amino group and a light response component to a biomass matrix and then curing the amino group and the light response component through a one-step rapid cross-linking strategy. The biomass-based adsorption material can be used for efficiently adsorbing hexavalent chromium and trivalent arsenic and converting hexavalent chromium and trivalent arsenic into trivalent chromium and pentavalent arsenic with low toxicity, so that synchronous removal and conversion are realized. The prepared biomass-based adsorption material can completely remove chromium and arsenic in water, meanwhile, the conversion rate of hexavalent chromium and the conversion rate of trivalent arsenic both reach 95% or above, a light source is effectively utilized, the synergistic effect between pollutants is amplified, the competitive effect is weakened, and global carbon emission reduction is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental governance, and specifically relates to a chromium and arsenic simultaneous removal-conversion biomass-based adsorption material and a preparation method and application thereof. Background Art

[0002] Chromium and arsenic are two of the most dangerous pollutants in industrial wastewater, posing a significant risk to groundwater resources and public health. Chromium and arsenic usually exist in the form of oxygenated anions, including hexavalent chromium, trivalent arsenic, and pentavalent arsenic, which often coexist in wastewater, especially from wood preservatives and acid mine drainage. Considering the high toxicity and high mobility of hexavalent chromium and trivalent arsenic, and the interaction between chromium and arsenic that increases the complexity of heavy metal wastewater treatment, achieving rapid adsorption of hexavalent chromium and trivalent arsenic and converting them into less toxic trivalent chromium and pentavalent arsenic is an effective water treatment strategy. Among the many wastewater treatment technologies, adsorption has become a green, low-carbon and sustainable wastewater treatment technology because its goal is consistent with "carbon neutrality". Among them, amino modification is considered to be a simple and effective method to improve the adsorption performance of oxygenated metal anions through electrostatic action. However, trivalent arsenic usually exists in an electrically neutral form, which limits the adsorption effect of amino-modified materials on it. In addition, hexavalent chromium and pentavalent arsenic compete for adsorption sites due to their similar electrical properties and adsorption mechanisms. Therefore, designing a material that can convert trivalent arsenic into pentavalent arsenic while improving the adsorption efficiency of chromium and arsenic is of great significance for the treatment of water bodies containing chromium and arsenic pollutants such as wood preservation wastewater and acidic mine drainage. Summary of the invention

[0003] The object of the present invention is to provide a chromium and arsenic simultaneous removal-conversion biomass-based adsorption material and a preparation method thereof. The material has abundant amino adsorption sites and good photothermal and photocatalytic properties, and can efficiently adsorb hexavalent chromium and trivalent arsenic while converting them into trivalent chromium and pentavalent arsenic with lower toxicity, thereby achieving simultaneous removal and conversion of hexavalent chromium and trivalent arsenic.

[0004] The above-mentioned purpose of the present invention is achieved by the following technical solutions:

[0005] The present invention provides a method for preparing a chromium and arsenic simultaneous removal-conversion type biomass-based adsorption material, which uses biomass as a matrix, introduces amino groups, reduced iron and coconut shell charcoal containing a C=C double bond into the biomass matrix through a ring-opening reaction of epichlorohydrin, and prepares the chromium and arsenic simultaneous removal-conversion type biomass-based adsorption material;

[0006] The preparation method of coconut shell charcoal containing C=C double bonds comprises: coconut shells are heated at 5-15°C·min under inert atmosphere. -1 The heating rate is raised to 600-900℃ and pyrolyzed for 45-130min; the pyrolysis product is mixed with KMnO4 The solutions were mixed and dried at 80-105°C; the dried mixture was mixed with NaOH or KOH and heated at 5-15°C·min -1 The heating rate is raised to 600-800°C for secondary pyrolysis, and the pyrolysis time is 60-120min; the secondary pyrolysis product is washed with water until the pH value is neutral, and then dried at 90-105°C to obtain coconut shell charcoal containing C=C double bonds, and the coconut shell charcoal is ball-milled to 300 mesh;

[0007] The amino group is derived from an amine compound.

[0008] Furthermore, the biomass is eucalyptus, pine, rice husk, straw or peanut shell, and the biomass is crushed to 200-400 mesh, cleaned, and then placed in an oven to dry.

[0009] Furthermore, the amine compound is polyethyleneimine, diethylenetriamine, tetraethylenepentamine, pentaethylenehexamine, polyallylamine or branched amine.

[0010] Furthermore, the coconut shell, KMnO 4 The addition ratio of solution, NaOH or KOH is 1.0g:0.5-2.5mL:0.3-2.0g, of which KMnO 4 The mass concentration of the solution is 0.3%-4.0%.

[0011] Furthermore, the preparation method of the above-mentioned chromium and arsenic simultaneous removal-conversion type biomass-based adsorption material mainly comprises the following operations: mixing biomass, amine compounds, coconut shell charcoal containing C=C double bonds, reduced iron powder and deionized water, and stirring at 200-600rpm for 5-25min; then adding epichlorohydrin to induce a cross-linking reaction until the mixture undergoes a liquid-solid conversion; washing the obtained solid product to neutrality and vacuum freeze-drying to obtain a chromium and arsenic simultaneous removal-conversion type biomass-based adsorption material.

[0012] Furthermore, the addition ratio of the biomass, amine compounds, coconut shell charcoal containing C=C double bonds, reduced iron powder, deionized water and epichlorohydrin is 1.0g:1.0-6.0g:1.0-3.0g:0.5-1.5g:10-28mL:3.0-10.0mL.

[0013] In addition, the present invention also provides a chromium and arsenic simultaneous removal-conversion biomass-based adsorption material prepared by the above preparation method.

[0014] In addition, the present invention also provides a use of a chromium and arsenic simultaneous removal-conversion biomass-based adsorption material prepared by the above preparation method in removing chromium and arsenic and reducing their toxicity. The chromium and arsenic simultaneous removal-conversion biomass-based adsorption material is placed in heavy metal wastewater containing chromium and arsenic, and under xenon lamp irradiation and stirring conditions, the adsorption material adsorbs hexavalent chromium and trivalent arsenic while converting the hexavalent chromium and trivalent arsenic into trivalent chromium and pentavalent arsenic with lower toxicity, respectively.

[0015] The present invention has the following beneficial effects:

[0016] (1) The biomass-based adsorption material prepared by the present invention has good photothermal and photocatalytic properties. Under the irradiation of light, the material not only heats up to above 60°C, but also generates photogenerated electrons that can convert hexavalent chromium into trivalent chromium and holes and hydroxyl radicals that can convert trivalent arsenic into pentavalent arsenic. The adsorption rate is increased while the conversion rate of hexavalent chromium and trivalent arsenic is enhanced.

[0017] (2) The one-step rapid cross-linking technology adopted in the present invention introduces reduced iron into the biomass-based adsorption material in the form of various iron oxides, and the iron component acts as an electronic bridge between hexavalent chromium and trivalent arsenic through the self-Fenton effect, further improving the conversion rate of hexavalent chromium and trivalent arsenic.

[0018] (3) The biomass-based adsorption material prepared by the present invention has abundant adsorption sites for anionic heavy metals (chromium, arsenic, etc.); the synergistic conversion between hexavalent chromium and trivalent arsenic is enhanced, and the hexavalent chromium preferentially adsorbed on the material not only enhances the conversion of trivalent arsenic, but also promotes the adsorption of pentavalent arsenic by enhancing the local electrical properties of the amino group.

[0019] (4) The biomass-based adsorption material prepared by the present invention can achieve rapid removal of chromium and arsenic in heavy metal wastewater (20-60 minutes), and the maximum adsorption capacity of chromium and arsenic is higher than 310 mg / L and 240 mg / L respectively. In addition, the chromium and arsenic enriched on the adsorption material mainly exist in the form of Cr(III) and As(V) with lower toxicity, and the conversion rates of hexavalent chromium and trivalent arsenic are both above 95%, achieving the simultaneous removal and conversion of hexavalent chromium and trivalent arsenic. DETAILED DESCRIPTION

[0020] The eucalyptus, pine and rice husks used in the following Examples 1-3 were all crushed, cleaned and then placed in an oven to dry.

[0021] Example 1

[0022] 1. Take 30g coconut shell and place it in a tube furnace under inert atmosphere at 15℃·min -1 The heating rate was raised to 800℃ and pyrolyzed for 60min. The pyrolysis products were mixed with KMnO 4(20.0 mL, 1 wt%) solution was mixed and dried at 80°C. The dried mixture was mixed with 45 g of KOH and heated at 10°C min -1 The heating rate was raised to 800°C for secondary pyrolysis, and the pyrolysis time was 60 min. The product was then washed with water until the pH value was neutral and dried at 95°C to obtain coconut shell charcoal containing C=C double bonds, which was ball-milled to 300 mesh.

[0023] 2. Eucalyptus (0.50 g, 200 mesh), polyethyleneimine (2.00 g), coconut shell charcoal containing C=C double bonds (1.00 g) and reduced iron powder (0.30 g) were mixed with 10.00 mL of deionized water and stirred at 200 rpm for 25 min. Subsequently, 2.00 mL of epichlorohydrin was added to initiate a crosslinking reaction until the mixture was liquid-solid transformed. The obtained solid sample was washed with deionized water to neutrality and vacuum freeze-dried to obtain a product, which was a eucalyptus-based adsorbent material for simultaneous removal and transformation of chromium and arsenic.

[0024] 0.05g of the eucalyptus-based adsorbent prepared in Example 1 was placed in a beaker containing 50mL of a chromium-arsenic mixed solution (Cr(VI) and As(III) concentrations were 50mg / L, respectively), and reacted on a magnetic stirrer at a speed of 180rmp under xenon lamp irradiation. Samples were taken every 10 minutes, 8mL of the solution was taken with a syringe and filtered using a 0.22μm water filter, and the resulting solution was measured for chromium and arsenic concentrations using ICP-OES. The chromium and arsenic concentrations in the sample were measured at 20min and 50min, respectively, and were both 0mg / L, that is, complete removal of chromium and arsenic was achieved. The XPS spectrum shows that the conversion rates of hexavalent chromium and trivalent arsenic on the eucalyptus-based adsorbent adsorbed with the chromium-arsenic mixed solution are 98.57% and 95.63%, respectively. The material was washed three times with 0.1M HCl solution and NaOH solution, and finally rinsed with clean water to a neutral pH value for a cyclic regeneration experiment. It was found that the eucalyptus-based adsorption material prepared in Example 1 could still achieve a removal rate of chromium and arsenic higher than 90% after five cycles. 1 g of the eucalyptus-based adsorption material prepared in Example 1 was placed in an adsorption column for a dynamic adsorption experiment, and its maximum adsorption capacity for hexavalent chromium and trivalent arsenic was measured to be 323 mg / L and 269 mg / L, respectively.

[0025] Example 2

[0026] 1. Take 30g coconut shell and place it in a tube furnace under inert atmosphere at 10℃·min -1 The heating rate was raised to 900℃ and pyrolyzed for 45min. The pyrolysis products were mixed with KMnO 4 (75.0 mL, 0.3 wt%) solution and dried at 95 °C. The dried mixture was mixed with 9 g of NaOH and heated at 15 °C min -1The heating rate was raised to 700°C for secondary pyrolysis, and the pyrolysis time was 90 min. The product was then washed with water until the pH value was neutral and dried at 90°C to obtain coconut shell charcoal containing C=C double bonds, which was ball-milled to 300 mesh.

[0027] 2. Pine wood (1.00 g, 300 mesh), polyethyleneimine (6.00 g), coconut shell charcoal containing C=C double bonds (3.00 g) and reduced iron powder (1.50 g) were mixed with 10.00 mL of deionized water and stirred at 300 rpm for 15 min. Then 3.0 mL of epichlorohydrin was added to initiate a crosslinking reaction until the mixture was liquid-solid transformed. The obtained solid sample was washed with deionized water to neutrality and vacuum freeze-dried to obtain a product, which was a pine wood-based adsorbent material for simultaneous removal and transformation of chromium and arsenic.

[0028] 0.05g of the pinewood-based adsorbent material prepared in Example 2 was placed in a beaker containing 50mL of a chromium-arsenic mixed solution (the concentrations of Cr(VI) and As(III) were 50mg / L, respectively), and reacted on a magnetic stirrer at a speed of 180rmp under the irradiation of a xenon lamp. Samples were taken every 10 minutes, and 8mL of the solution was taken with a syringe and filtered using a 0.22μm water filter. The resulting solution was measured for the concentrations of chromium and arsenic using ICP-OES. The concentrations of chromium and arsenic in the sample were measured at 30min and 50min, respectively, and were both 0mg / L, that is, the complete removal of chromium and arsenic was achieved. The XPS spectrum shows that the conversion rates of hexavalent chromium and trivalent arsenic on the pinewood-based adsorbent material adsorbed with the chromium-arsenic mixed solution are 96.74% and 96.88%, respectively. The material was washed three times with 0.1M HCl solution and NaOH solution, and finally rinsed with clean water to a neutral pH value for a cyclic regeneration experiment. It was found that the pine wood-based adsorption material prepared in Example 2 could still achieve a removal rate of chromium and arsenic higher than 90% after five cycles. 1 g of the pine wood-based adsorption material prepared in Example 2 was placed in an adsorption column for a dynamic adsorption experiment, and its maximum adsorption capacity for hexavalent chromium and trivalent arsenic was measured to be 313 mg / L and 282 mg / L, respectively.

[0029] Example 3

[0030] 1. Take 30g coconut shell and place it in a tube furnace under inert atmosphere at 5℃·min -1 The heating rate was raised to 600℃ and pyrolyzed for 130min. The pyrolysis products were mixed with KMnO 4 (15.0 mL, 4.0 wt%) solution and dried at 105 °C. The dried mixture was mixed with 60 g of KOH and heated at 5 °C min -1The heating rate was raised to 600°C for secondary pyrolysis, and the pyrolysis time was 120 min. The product was then washed with water until the pH value was neutral and dried at 105°C to obtain coconut shell charcoal containing C=C double bonds, which was ball-milled to 300 mesh.

[0031] 2. Rice husk (1.00 g, 400 mesh), polyethyleneimine (1.00 g), coconut shell charcoal containing C=C double bonds (1.00 g) and reduced iron powder (0.50 g) were mixed with 28.00 mL of deionized water and stirred at 600 rpm for 5 min. Then 10.00 mL of epichlorohydrin was added to initiate a crosslinking reaction until the mixture was liquid-solid transformed. The obtained solid sample was washed with deionized water to neutrality and vacuum freeze-dried to obtain a product, which was a rice husk-based adsorbent material for simultaneous removal and transformation of chromium and arsenic.

[0032] 0.05 g of the rice husk-based adsorbent material prepared in Example 3 was placed in a beaker containing 50 mL of a chromium-arsenic mixed solution (the concentrations of Cr(VI) and As(III) were 50 mg / L, respectively), and reacted on a magnetic stirrer at a speed of 180 rpm under the irradiation of a xenon lamp. Samples were taken every 10 minutes, and 8 mL of the solution was taken with a syringe and filtered using a 0.22 μm water filter. The resulting solution was measured for the concentrations of chromium and arsenic using ICP-OES. The concentrations of chromium and arsenic in the sample were measured at 20 minutes and 60 minutes, respectively, and were both 0 mg / L, that is, the complete removal of chromium and arsenic was achieved. The XPS spectrum shows that the conversion rates of hexavalent chromium and trivalent arsenic on the rice husk-based adsorbent material adsorbed with the chromium-arsenic mixed solution are 99.21% and 95.13%, respectively. The material was washed three times with 0.1M HCl solution and NaOH solution, and finally rinsed with clean water to a neutral pH value for a cyclic regeneration experiment. It was found that the rice husk-based adsorption material prepared in Example 3 could still achieve a removal rate of chromium and arsenic higher than 90% after five cycles. 1 g of the rice husk-based adsorption material prepared in Example 3 was placed in an adsorption column for a dynamic adsorption experiment, and its maximum adsorption capacity for hexavalent chromium and trivalent arsenic was measured to be 332 mg / L and 246 mg / L, respectively.

[0033] Comparative Example 1

[0034] 1. Same as step 1 of Example 1.

[0035] 2. Polyethyleneimine (2.00 g), coconut shell charcoal containing C=C double bonds (1.00 g) and reduced iron powder (0.30 g) were mixed with 10.00 mL of deionized water and stirred at 200 rpm for 25 min. Subsequently, 2.00 mL of epichlorohydrin was added to initiate a crosslinking reaction until the mixture was liquid-solid transformed. The obtained solid sample was washed with deionized water until neutral and the product was obtained by vacuum freeze drying, which was a carbon-based adsorption material.

[0036] 0.05g of the carbon-based adsorption material prepared in Comparative Example 1 was placed in a beaker containing 50mL of a chromium-arsenic mixed solution (the concentrations of Cr(VI) and As(III) were 50mg / L, respectively), and reacted on a magnetic stirrer at a speed of 180rmp under the irradiation of a xenon lamp. Samples were taken every 10 minutes, and 8mL of the solution was taken with a syringe and filtered using a 0.22μm water filter. The resulting solution was measured for the concentrations of chromium and arsenic using ICP-OES. The concentrations of chromium and arsenic in the sample were measured at 20min and 50min, respectively, to be 0.223mg / L and 13.926mg / L, respectively. Compared with Example 1, the carbon-based adsorption material of Comparative Example 1 had a poor removal effect on chromium and arsenic. The material was washed three times with 0.1M HCl solution and NaOH solution, and finally rinsed with clean water to a neutral pH value for a cyclic regeneration experiment. It was found that the carbon-based adsorption material prepared in Comparative Example 1 had a removal effect of 85% and 67% of chromium and arsenic, respectively, when it was recycled for the third time, which was significantly lower than that of Example 1.

[0037] Comparative Example 2

[0038] 1. Same as step 1 of Example 1.

[0039] 2. Eucalyptus (0.50 g, 200 mesh), polyethyleneimine (2.00 g) and coconut shell charcoal containing C=C double bonds (1.00 g) were mixed with 10.00 mL of deionized water and stirred at 200 rpm for 25 min. Subsequently, 2.00 mL of epichlorohydrin was added to initiate a crosslinking reaction until the mixture was liquid-solid transformed. The obtained solid sample was washed with deionized water until neutral and vacuum freeze-dried to obtain the product, which was the eucalyptus-based adsorption material.

[0040] 0.05g of the eucalyptus-based adsorbent prepared in Comparative Example 2 was placed in a beaker containing 50mL of a chromium-arsenic mixed solution (Cr(VI) and As(III) concentrations were 50mg / L, respectively), and reacted on a magnetic stirrer at a speed of 180rmp under xenon lamp irradiation. Samples were taken every 10 minutes, 8mL of the solution was taken with a syringe and filtered using a 0.22μm water filter head, and the resulting solution was measured for chromium and arsenic concentrations using ICP-OES. The chromium and arsenic concentrations in the sample were measured at 30min and 60min, respectively, and the arsenic removal effect was poor. The XPS spectrum showed that the conversion rates of hexavalent chromium and trivalent arsenic on the eucalyptus-based adsorbent adsorbed with the chromium-arsenic mixed solution were 72.65% and 25.77%, respectively.

Claims

1. A method for preparing a chromium and arsenic simultaneous removal-conversion type biomass-based adsorption material, characterized in that: Taking biomass as a matrix, amino groups, reduced iron and coconut shell charcoal containing C=C double bonds are introduced into the biomass matrix through the ring-opening reaction of epichlorohydrin to prepare the chromium and arsenic simultaneous removal-conversion biomass-based adsorption material; The preparation method of coconut shell charcoal containing C=C double bonds comprises: coconut shells are heated at 5-15°C·min under inert atmosphere. -1 The heating rate is raised to 600-900℃ and pyrolyzed for 45-130min; the pyrolysis product is mixed with KMnO4 solution and dried at 80-105℃; the dried mixture is mixed with NaOH or KOH and heated at 5-15℃·min -1 The heating rate is raised to 600-800°C for secondary pyrolysis, and the pyrolysis time is 60-120min; the secondary pyrolysis product is washed with water until the pH value is neutral, and then dried at 90-105°C to obtain coconut shell charcoal containing C=C double bonds, and the coconut shell charcoal is ball-milled to 300 mesh; The amino group is derived from an amine compound.

2. The preparation method according to claim 1, characterized in that: The biomass is eucalyptus, pine, rice husk, straw or peanut shell. The biomass is crushed to 200-400 meshes, cleaned, and then placed in an oven to dry.

3. The preparation method according to claim 1, characterized in that: The amine compound is polyethyleneimine, diethylenetriamine, tetraethylenepentamine, pentaethylenehexamine, polyallylamine or branched amine.

4. The preparation method according to claim 1, characterized in that: The added amount ratio of the coconut shell, KMnO4 solution, and NaOH or KOH is 1.0 g: 0.5-2.5 mL: 0.3-2.0 g, wherein the mass concentration of the KMnO4 solution is 0.3%-4.0%.

5. The preparation method according to claim 1, characterized in that: The main operation is: biomass, amine compounds, coconut shell charcoal containing C=C double bonds, reduced iron powder and deionized water are mixed and stirred at 200-600rpm for 5-25min; epichlorohydrin is then added to initiate a cross-linking reaction until the mixture undergoes a liquid-solid conversion; the obtained solid product is washed to neutrality and vacuum freeze-dried to obtain a chromium and arsenic simultaneous removal-conversion biomass-based adsorption material.

6. The preparation method according to claim 5, characterized in that: The addition ratio of the biomass, the amine compound, the coconut shell charcoal containing C=C double bonds, the reduced iron powder, the deionized water and the epichlorohydrin is 1.0g:1.0-6.0g:1.0-3.0g:0.5-1.5g:10-28mL:3.0-10.0mL.

7. A chromium and arsenic simultaneous removal-conversion type biomass-based adsorption material prepared by the preparation method according to any one of claims 1 to 6.

8. Use of a chromium and arsenic simultaneous removal-conversion type biomass-based adsorption material prepared by the preparation method according to any one of claims 1 to 6 in removing chromium and arsenic and reducing their toxicity.

9. The use according to claim 8, characterized in that: The chromium and arsenic simultaneous removal-conversion biomass-based adsorption material is placed in heavy metal wastewater containing chromium and arsenic. Under xenon lamp irradiation and stirring conditions, the adsorption material adsorbs hexavalent chromium and trivalent arsenic while converting the hexavalent chromium and trivalent arsenic into less toxic trivalent chromium and pentavalent arsenic respectively.

Citation Information

Patent Citations

  • Biomass resin based inorganic nano-oxide composite adsorbent and preparation method and application thereof

    CN104353440A

  • Preparation method of arsenic removal adsorbing agent with photo-catalytic oxidation and adsorption effect

    CN105854845A

  • Preparation method and applications of shaddock peel-modified amino functionalized adsorbent

    CN106179239A

  • Magnetic biomass functional carbon fiber based on photo-Fenton catalysis, preparation method and application thereof

    CN110330091A

  • Preparation method and application of iron and manganese oxide biochar composite material

    CN116870865A